ANALISIS PENGARUH STRES KERJA DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN (Studi Pada STIKES Widya Husada Semarang) - Tiorina Manurung, Mona; Ratnawati, Intan (Faculty of Economics and Business Diponegoro University, 2012)
Performance of a company is determined by the condition and behavior of employees who owned company. One form of employee behavior that can not be prevented the occurrence of a desire to move (turnover intention) that led to the employee's decision to leave her job. High employee turnover rate may result in the organization becomes ineffective because the company loses experienced employees and the need to retrain new employees. This study aims to analyze the influence of the variables of job stress and job satisfaction on turnover intention of employees. The research was conducted in STIKES Widya Husada Semarang. The number of samples set at 98 respondents to the census methods and data analysis method used is multiple linear regression analysis using SPSS. The results of testing of the hypothesis, suggesting that job stress variables have a positive effect on employee turnover intention. Job satisfaction is negatively affecting the turnover intention of employees. The results of a small coefficient of determination indicates that the ability of the independent variables (job stress and job satisfaction) in explaining the dependent variable (turnover intention of employees) is very limited.